Interaction of catalase with carrageenan applied to its recovery from murine liver - Belluzo, María Soledad (2013)
The complexes formation between acid and basic polyelectrolytes (carrageenan and Eudragit ® EPO) with catalase was evaluated in order to understand the mechanism of their interaction. Catalase was selected as the model enzyme since its application in several biotechnological processes. The study of this interaction had showed that the non soluble complexes take place in a pH interval which depends on the nature of the polyelectrolyte and salt presence. Carrageenan showed to be the best choice for the catalase affinity precipitation, since the amount needed for the full precipitation of the enzyme was lower, with a faster kinetic and a slight stabilization of the protein structure. After establishing the optimal conditions, we were able to purify catalase from murine liver, a natural source, with a purification factor of 6.4 and a yield of 19%, using only one step in the enzyme purification process.